The Characterization of RNA Viruses in Tropical Seawater Using Targeted PCR and Metagenomics - Culley, Alexander I. (American Society of Microbiology, 2014)
Viruses have a profound influence on the ecology and evolution of plankton, but our understanding of the composition of the aquatic viral communities is still rudimentary. This is especially true of those viruses having RNA genomes. The limited data that have been published suggest that the RNA virioplankton is dominated by viruses with positive-sense, single-stranded (+ss) genomes that have features in common with those of eukaryote-infecting viruses in the order Picornavirales (picornavirads). In this study, we investigated the diversity of the RNA virus assemblages in tropical coastal seawater samples using targeted PCR and metagenomics. Amplification of RNA-dependent RNA polymerase (RdRp) genes from fractions of a buoyant density gradient suggested that the distribution of two major subclades of the marine picornavirads was largely congruent with the distribution of total virus-like RNA, a finding consistent with their proposed dominance. Analyses of the RdRp sequences in the library revealed the presence of many diverse phylotypes, most of which were related only distantly to those of cultivated viruses. Phylogenetic analysis suggests that there were hundreds of unique picornavirad-like phylotypes in one 35-liter sample that differed from one another by at least as much as the differences among currently recognized species. Assembly of the sequences in the metagenome resulted in the reconstruction of six essentially complete viral genomes that had features similar to viruses in the families Bacillarna-, Dicistro-, and Marnaviridae. Comparison of the tropical seawater metagenomes with those from other habitats suggests that +ssRNA viruses are generally the most common types of RNA viruses in aquatic environments, but biases in library preparation remain a possible explanation for this observation.